Islamic Republic of Iran : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2010)
This Selected Issues paper discusses the economics of energy price reform in the Islamic Republic of Iran. Economic policies in Iran have traditionally relied on the abundant availability of energy at a low price to finance the country's economic development. Low domestic energy prices have resulted in excessive use of energy. Iran's domestic energy use has been high by international standards, and energy demand growth has exceeded the rate of growth of per capita income, in contrast to the experience of the majority of low and high-income countries.